Linguagem de programação Python e Arduino como ferramenta para motivar estudantes iniciantes em programação - Guedes, Danila Branco (2018)
Over the course of several years, programming has been taking up space, increasing the use of technology as a whole, with a great opportunity in this area of knowledge. Thus, the objectives of this course completion work are: to motivate and expand the knowledge of beginning students in the programming area; demonstrate the ease of working with the Python programming language; demonstrate the practicality of working with Arduino technology. In order to reach such objectives, a case study was carried out using the serial communication between Python and Arduino.